Media Pictory (Picture Trip Story) Berbantuan Toefl Diagram untuk Meningkatkan Keterampilan Menulis Teks Recount - Awaliyah, Imatul (Jurnal Didaktika Pendidikan Dasar, 2023)
Learning English at SMP Negeri 1 Gondang has not been able to improve recount text writing skills. Students’ writing skill in VIII I class still needs to be improved. The teacher conducts class action by creating Pictory Picture Trip Story media combined with TOEFL (Title Orientation Events Feeling Last) diagrams. This classroom action research was conducted in two cycles. At the end of the action, students' writing recount text skills increased from an average of 73 in pre-cycle to 80.In short, it can be concluded that the use of Pictory  assisted with TOEFL diagram can improve students’ writing skills of recount text in VIII I class 2019/2020 academic year.